Pengaruh Iklim Organisasi, Kesehatan Dan Tingkat Absensi Terhadap Prestasi Kerja Karyawan (Studi Pada Karyawan Telkom Indonesia di Surakarta) - Amorita, Tania, Imron Rosyadi, SE.,M.Si (2017)
Purposes of the research were to know: (1) effect of organizational climate on performance of employee, (2) effect of health on performance of employee, (3) level of absenteeism on performance of employee, (4) variable with dominant effect on performance of employees in Telkom Indonesia, Surakarta. The research is qualitative one. Sample of the research was employees of Telkom Indonesia of Surakarta amounting to 95 respondents and data was collected by using questionnaire. The data was analyzed by using multiple linear regression, classic assumption test, t-test, F-test and coefficient of determination (R2). Results of the research indicated that partial effect between independent and dependent variables was found. Data analysis of F-test showed simultaneous effect of organizational climate, health and level of absenteeism on performance of employee. Coefficient of regression indicated that regression variable of organizational climate had dominant effect than health and level of absenteeism on performance of employee.